Role of Fecal Diversion in Complex Crohn's Disease - Burke, John P. (Clinics in Colon and Rectal Surgery, 2019)
Crohn's disease (CD) is a chronic inflammatory condition of the gastrointestinal tract resulting in progressive tissue damage, which can result in strictures, fistulae, and abscesses formation. The triggering mechanism is thought to be in the fecal stream, and diversion of this fecal stream is sometimes required to control disease when all other avenues of medical and surgical management have been exhausted. Fecal diversion can be temporary or permanent with the indications being defunctioning a high-risk anastomosis, as a result of a surgical complication, for disease control, or due to severe colonic, rectal, or perianal disease. The incidence of ostomy formation in CD has increased epidemiologically over time. The primary indication for ostomy formation is severe perianal fistulizing disease. However, while 64% of patients have an early clinical response after diversion for refractory perianal CD, restoration of bowel continuity is attempted in only 35% of patients, and is successful in only 17%. The current review discusses the indications for ostomy creation in complex CD, strategies for procedure selection, and patient outcomes.
Keywords: Crohn's disease; ileostomy; colostomy; ostomy; stoma; fistula; abscess; stricture; colitis